Study of the effect of milk protein preparations on model mincemeat of chopped semi-finished products - Haschuk, Olexandra; Moskaluyk, Oksana; Vernyhora, Anna (My University, 2023)
М’ясний фарш належить до систем з коагуляційною структурою, частинки якої зв’язані у суцільний каркас силами міжмолекулярної взаємодії. Відомо, що білки тваринного походження мають більші сили взаємодії ніж рослинні. Частина яловичини, яка надає фаршу в’язкості, замінена на молочний білок, у якого значно менша сила взаємодії між частинками. Молочний білок рівномірно розміщується між частинками м’язової тканини, збільшуючи відстань між ними. Для максимального збільшення вологозв’язуючої здатності м’яса рекомендована доза додавання сухих молочних білків становить 0,1... 1,0%. Із збільшенням кількості молока спостерігається погіршення водозв'язуючої здатності. Minced meat belongs to systems with a coagulation structure, the particles of which are bound into a solid frame by the forces of intermolecular interaction. It is known that proteins of animal origin have greater interaction forces than plant proteins. The part of beef that gives the minced meat viscosity is replaced by milk protein, which has a much lower strength of interaction between particles. Milk protein is evenly placed between the particles of muscle tissue, increasing the distance between them. To maximize the moisture-binding capacity of meat, the recommended dose of adding dry milk proteins is 0.1...1.0%. With an increase in the amount of milk, there is a deterioration of the water-binding capacity.
Keywords: препарати молочних білків; модельні фарші посічених напівфабрикатів; milk protein preparations; model mincemeat of chopped semi-finished products; кафедра технології м’яса і м’ясних продуктів